2017
DOI: 10.3389/fnins.2017.00475
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Pulsations cannot Drive Intramural Periarterial Drainage: Significance for Aβ Drainage

Abstract: Alzheimer's Disease (AD) is the most common form of dementia and to date there is no cure or efficient prophylaxis. The cognitive decline correlates with the accumulation of amyloid-β (Aβ) in the walls of capillaries and arteries. Our group has demonstrated that interstitial fluid and Aβ are eliminated from the brain along the basement membranes of capillaries and arteries, the intramural periarterial drainage (IPAD) pathway. With advancing age and arteriosclerosis, the stiffness of arterial walls, this pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 27 publications
3
96
1
Order By: Relevance
“…Later notable insights were provided by (1) Wagner (1974) [185] and Rennels (1985) [148], who showed that CSFinfused substances may be capable of reaching the PVS of capillaries, (2) Rosenberg [150] and Konsman [104], who demonstrated the involvement of the white matter as a bulk flow pathway for CSF-infused substances, (3) Patlak (1970, 1975) [111,135], Rosenberg (1980) [150], Ghersi-Egea (1996) [68], and Proescholdt (2000) [142], who performed experiments where the penetration of CSFinfused tracers across the brain-CSF interfaces appeared consistent with diffusive transport, and (4) Krisch (1983Krisch ( , 1984 [107,108] and Ichimura (1991) [88], who demonstrated communication between the ECS, PVS, subpial space, and subarachnoid trabeculae core following CSF infusion of tracer. It must be noted that the group of Weller and Carare have interpreted a number of their own more recent studies injecting tracers into the brain parenchyma as suggesting outward directed flow of ISF/solutes primarily confined to the capillary basal lamina and the smooth muscle basement membrane (tunica media) of arterioles/ arteries [24,120], a process they have termed an 'intramural peri-arterial drainage' pathway [48,58]. Nevertheless, most experimental work and modelling to date has been interpreted as supporting some type of inward transport process from the CSF to the brain within the vascular connective tissue space of the tunica adventitia of arteries and arterioles (see [1,77,137] for more discussion).…”
Section: Blood Vessels and The Perivascular Spacementioning
confidence: 99%
“…Later notable insights were provided by (1) Wagner (1974) [185] and Rennels (1985) [148], who showed that CSFinfused substances may be capable of reaching the PVS of capillaries, (2) Rosenberg [150] and Konsman [104], who demonstrated the involvement of the white matter as a bulk flow pathway for CSF-infused substances, (3) Patlak (1970, 1975) [111,135], Rosenberg (1980) [150], Ghersi-Egea (1996) [68], and Proescholdt (2000) [142], who performed experiments where the penetration of CSFinfused tracers across the brain-CSF interfaces appeared consistent with diffusive transport, and (4) Krisch (1983Krisch ( , 1984 [107,108] and Ichimura (1991) [88], who demonstrated communication between the ECS, PVS, subpial space, and subarachnoid trabeculae core following CSF infusion of tracer. It must be noted that the group of Weller and Carare have interpreted a number of their own more recent studies injecting tracers into the brain parenchyma as suggesting outward directed flow of ISF/solutes primarily confined to the capillary basal lamina and the smooth muscle basement membrane (tunica media) of arterioles/ arteries [24,120], a process they have termed an 'intramural peri-arterial drainage' pathway [48,58]. Nevertheless, most experimental work and modelling to date has been interpreted as supporting some type of inward transport process from the CSF to the brain within the vascular connective tissue space of the tunica adventitia of arteries and arterioles (see [1,77,137] for more discussion).…”
Section: Blood Vessels and The Perivascular Spacementioning
confidence: 99%
“…Intramural periarterial drainage (IPAD) is hypothesized to be a major pathway by which waste products, such as Aβ, are drained from the brain (Bakker et al, 2016;Morris et al, 2016;Saito et al, 2019). Theoretical modeling studies suggested that the motive force for IPAD is derived from vascular smooth muscle contractions and biochemical interactions with basement membranes (Diem et al, 2017). We reported cilostazol promoted the IPAD and ameliorated cerebrovascular Aβ pathology by using Tg-SwDI mice, a mouse model of Alzheimer's disease (Maki et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…PVS changes have been linked to vascular diseases, including cerebral small vessel disease, cerebral amyloid angiopathy, BBB breakdown, hypertension and lacunar stroke [1,[11][12][13][14][15][16][17]. Furthermore, an emerging body of evidence suggests vascular changes are linked to both clearance system dysfunction [18][19][20][21][22][23] and vasculotoxic effects of A and tau [10,24].…”
Section: Introductionmentioning
confidence: 99%